The Quality of Kiserian Slaughterhouses' Effluent and Its Implication on Kiserian Dam Water in Kajiado County, Kenya - Ngare, Leah; Kitur, Esther (International Journal of Environmental Sciences, 2023)
Purpose: Wastewater from abattoirs, municipal, agricultural and industrial effluents is a major source of environmental pollution as they consume large amounts of fresh water for meat processing and hygienic purposes. The main objective of the study was to assess the quality of the effluent from Keekonyokie and Kiserian slaughterhouses and its effect on the quality of water in Kiserian dam. Methodology: The parameters measured were pH, total suspended solids, total nitrogen, total phosphorous, dissolved oxygen and fecal coliforms (E. coli). Samples were collected from 4 sampling sites three times a week for three months. SPSS (ANOVA) for their significant differences. One-sample t-test used to compare the parameter means with NEMA 2006 standards. Pearson Correlation used for correlation among the parameters. Findings: The mean fecal coliforms 2215.206 mg/l, Phosphorous 47.379 mg/l, Nitrates 36.71 mg/l, TSS 387.57 mg/l which were above the standards of NEMA 2006 of nil, 2, 2 and 30 mg/l respectively while DO was 8.58 mg/l and pH 6.86-7.0 both of which were below the NEMA 2006 standards of 30 mg/l and 6.5-8.5. The results of all parameters were significantly different among the sites (p=0.00). There was significant difference between the parameters and the NEMA 2006. ANOVA results on parameters showed the all coliforms increased with increase in rainfall with the highest levels in September with a mean 18662.7 mg/l and in July with the lowest of 12962.5 mg/l. Unique Contribution to Theory, Practice and Policy: The study can be used by slaughterhouses developers and management on slaughterhouse wastewater treatment. To be used by slaughterhouses licensing authorities on SWW requirements before licensing. To be used by Public Health Department for disease surveillances and Water Regulatory Management Authority on domestic water treatment.